Exploring the Challenges of Implantable Antennas in Capsule Endoscopy Applications: An Overview - Suryanata, Faishal Adilah; Dewan, Raimi; Paramasivam, DiviyaDevi; Sim, Man Seng; Tan, Tian Swee; Hamid, Mohamad Rijal (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Antennas play a crucial role in implantable medical devices (IMDs), particularly in applications such as gastric endoscopy. Therefore, this paper reviews recent advancements in antenna design for IMDs, focusing on the benefits and challenges. The findings from recent research will serve as a reference for future studies, emphasizing the need to address existing challenges. Specifically, this paper investigates the miniaturization and signal performance of the antenna when simulated inside the human body and explores the potential solutions for the challenges. Additionally, this paper discusses various gastric diseases, the development of gastric body phantoms, and relevant studies from reputable journals. Finally, the future directions for further improvement of the research are being discussed.